Turnover Intention on Employees of Start-Up Companies: Subjective Fit Perception, Personal Resources and Job Insecurity with Work Engagement - Kholda Anastaya Burhannudin; Fanny Martdianty (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Purpose – Human resources are a crucial aspect of start-up companies, representing both a significant investment and a valuable asset. This paper explored an integrative model that investigates how work engagement mediates the impact of job insecurity, person-organization fit, and person-job fit. Methodology – Responses were collected using an online questionnaire at Indonesia start-up company from 317 employees. To evaluate the model's overall fit and the causal relationships between the constructs, Structural Equation Modeling (SEM) was employed. Findings – The study findings revealed that among employees in start-up companies, the influence of job insecurity and person-organization fit on turnover intention is fully mediated by work engagement. Additionally, work engagement partially mediates the relationship between job insecurity and person-job fit on turnover intention. The study suggests that companies should ensure job security for their employees and emphasize their significance within the organization. Furthermore, companies should offer activities to enhance employee competencies. Originality –This study will examine differences in the intensity of this effect based on the gender of employees at start-up companies